Nonsyndromic Split-Hand/Foot Malformation: Recent Classification - Umair, Muhammad (Mol Syndromol, 2020)
Split-hand/foot malformation (SHFM) is a genetic limb anomaly disturbing the central rays of the autopod. SHFM is a genetically heterogeneous disorder with variable expressivity inherited as syndromic and nonsyndromic forms. We provide an update of the clinical and molecular aspects of nonsyndromic SHFM. This rare condition is highly complex due to the clinical variability and irregular genetic inheritance observed in the affected individuals. Nonsyndromic SHFM types have been reviewed in terms of major molecular genetic alterations reported to date. This updated overview will assist researchers, scientists, and clinicians in making an appropriate molecular diagnosis, providing an accurate recurrence risk assessment, and developing a management plan.